Staphylococcus aureus pada keyboard di unit pelayanan penunjang rumah sakit - Deby Arnisya Putri; Erpan Roebiakto; Ratih Dewi Dwiyanti (Jurnal Skala Kesehatan, 2018)
Computer keyboard can be a cause of health problems due to poor cleanliness. Keyboard that is not cleaned contains more bacteria. Staphylococcus aureus is one of the bacteria that causes nosocomial infection that can be found on the keyboard. The purpose of this research is to know the description of Staphylococcus aureus bacteria in Hospital Supporting Unit. This type of research is descriptive survey with 16 samples with total sampling. Based on research conducted on the keyboard in the Medical Support Unit Hospital found Staphylococcus aureus as much as 68.75% It is recommended to do keyboard cleanliness and cleanliness of computer users before and after using the computer.